TUIMP: The Universe In My Pocket. Free astronomy booklets in all languages - Stasinska, G.
TUIMP (www.tuimp.org) is an international project to produce little astronomy booklets. These booklets, folded from just one sheet of paper, can be used in classrooms, at open public conferences, or during visits of observatories and planetariums. They are free to download from the internet, the only thing which is needed is a color printer (in absence of a printer, the booklets can also be directly consulted on line, even with just a mobile phone). The booklets are intended for children from nine years old and for anyone curious of astronomy. They are written in a simple language, amply illustrated, revised and translated by professional astronomers. So far, they are being published in six languages, others languages are to come. Everyone is invited to download the booklets and use them in their outreach activities.
Keywords: Astronomy